Aplikasi Pendataan Penduduk Desa Dindey Berbasis Web: Web-Based Village Population Data Application For Dindey Village - Cony Mambraku; Julius Panda Putra Naibaho; Cristian Dwi Suhendra (JISTECH: Journal of Information Science and Technology, 2023)
The population data information system at the village level in Dindey still relies on a manual system where only family cards, ID cards, and other documents are collected and stored in village cabinets. This has caused several inconvenient issues, especially regarding the storage of population data. There are often difficulties in searching for information about new residents or residents who have moved away from the village. Considering these challenges, a web-based application using PHP programming language and MySQL titled "Web-Based Population Data Collection Application for Dindey Village" is needed to assist the village government in conducting population data collection in the village. The research method employed in this study is the Waterfall method. The results of this study indicate that the application is accessible, and the features within the Population Data Collection Application for Dindey Village function properly.